Three-Dimensional Stress State Around Corrosive Cavities on Pressure Vessels - Abdulaliyev, Z.; Ataoglu, S.; Bulut, O.; Kayali, E. S. (ASME International, 2010)
Internal surfaces of pressure vessels used in many industrial sectors are subjected to corrosive effects leading to cavities. In this study, corrosive cavities on investigated pressure vessels are classified according to their shapes and dimensions. Distribution of stress was experimentally investigated around regions of different types of cavities using three-dimensional photoelastic models. An empirical expression is proposed to determine where maximum stress occurs in type of ellipsoidal cavity in the case of uniaxial loading. The obtained results show quite high stress levels around the cavity regions in pressure vessels, which increase the risk of crack formation.